Neutrinos from Cosmic Accelerators including Magnetic Field and Flavor Effects - Walter Winter (Advances in High Energy Physics)
We review the particle physics ingredients affecting the normalization, shape, and flavor composition of astrophysical neutrinos fluxes, such as different production modes, magnetic field effects on the secondaries (muons, pions, and kaons), and flavor mixing, where we focus on pγ interactions. We also discuss the interplay with neutrino propagation and detection, including the possibility to detect flavor and its application in particle physics, and the use of the Glashow resonance to discriminate pγ from pp interactions in the source. We illustrate the implications on fluxes and flavor composition with two different models: (1) the target photon spectrum is dominated by synchrotron emission of coaccelerated electrons and (2) the target photon spectrum follows the observed photon spectrum of gamma-ray bursts. In the latter case, the multimessenger extrapolation from the gamma-ray fluence to the expected neutrino flux is highlighted.